PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN KONSUMEN DALAM MEMBELI DI HEMA RESTO KEMANG PRATAMA BEKASI - Mirantika, Sefti Dwi; Khadijah, Siti (Fakultas Komunikasi, Sastra, dan Bahasa, 2015)
Marketing communication strategies are important guidelines to introduce, give informations and market products in a company that can not be separated from the role marketing mix as the core of a marketing system. It takes some diligence and foresight to know what consumers desire for in a restaurant, such as HEMA Resto Dutch restaurant. As a result, HEMA should be able to attract consumers' attention from the product, price, place and promotion. This study aims to analyze the effect of the implementation of the marketing mix including product policy, price, place and promotion of consumer buying decisions in the HEMA restaurant. Research conduced in June-July 2012 at the HEMA Resto Kemang Pratama, methods used is case study. Method of determining the location Judgesment Sampling is based on several criteria, namely: Consumer HEMA Resto Kemang Pratama, 17-50 years of age or older, was selected because of HEMA Resto Kemang Bekasi. Determination of Sampling Methods using the Slovin formula, where the consumer is taken as the respondents were 100 people, the primary obtained data questionnaires and interviews with respondents and restaurant marketing manager. The results of multiple linear regression analysis by simultaneously obtained Fhitung> F  table is  41.544> 2.70  means  the  marketing  mix  variables  simultaneously influencing consumer buying decisions. Of partial regression test for the product (X1) is obtained 9.072 t count <t chart 1.98498. Price (X2) t count 4.975 <t chart 1.98498. Place (X3) t count -1, 846> t table 1.98498. Promotion (X4) t count 0.739 <t chart 1.98498. partial product pricing policy and influence buying decisions, while place and promotion policies have no effect on consumer buying decisions